(untitled) (Academicia Globe: Inderscience Research, 2023)
This article examines the role of the court and Islamic religious authorities in the fight against religious extremism and terrorism in Malaysia. The judiciary has a duty to protect people, guarantee freedom and administer justice. It is the constitutional duty of the Islamic religious authorities to preserve religion, protect Muslims and isolate the teachings of Islam in Malaysia. Under the country’s federal constitutional system, the civil court and the federal government do not deal with religious matters, as they fall under the jurisdiction of sharia law and state sharia courts. In order to counter terrorist threats and counter the spread of dangerous extremist ideologies, the court and Islamic religious authorities need to have mutual understanding and cooperation in achieving a common goal. Only then will the fight against religious extremism and terrorism in Malaysia be sustainable and effective.